2022
DOI: 10.3390/cancers14081873
|View full text |Cite
|
Sign up to set email alerts
|

Early T-Cell Precursor ALL and Beyond: Immature and Ambiguous Lineage T-ALL Subsets

Abstract: A wide range of immature acute leukemias (AL), ranging from acute myeloid leukemias with minimal differentiation to acute leukemias with an ambiguous lineage, i.e., acute undifferentiated leukemias and mixed phenotype acute leukemia with T- or B-plus myeloid markers, cannot be definitely assigned to a single cell lineage. This somewhat “grey zone” of AL expresses partly overlapping features with the most immature forms of T-cell acute lymphoblastic leukemia (T-ALL), i.e., early T-cell precursor ALL (ETP-ALL), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 89 publications
(150 reference statements)
0
11
0
Order By: Relevance
“…Heterogeneous group accounting for 15% of childhood and 25% of adult T-ALLs [21,38–40,41 ▪▪ ]. In 40–45% of immature cases the poor prognostic HOXA-positive subgroup is marked by rearrangements at HOXA cluster or at NUP214 , NUP98 , MLLT10 , and KMT2A gene, in a mutually exclusive manner [42–46].…”
Section: Immature T-cell Acute Lymphoblastic Leukemias (Etp-all Near ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneous group accounting for 15% of childhood and 25% of adult T-ALLs [21,38–40,41 ▪▪ ]. In 40–45% of immature cases the poor prognostic HOXA-positive subgroup is marked by rearrangements at HOXA cluster or at NUP214 , NUP98 , MLLT10 , and KMT2A gene, in a mutually exclusive manner [42–46].…”
Section: Immature T-cell Acute Lymphoblastic Leukemias (Etp-all Near ...mentioning
confidence: 99%
“…In 40–45% of immature cases the poor prognostic HOXA-positive subgroup is marked by rearrangements at HOXA cluster or at NUP214 , NUP98 , MLLT10 , and KMT2A gene, in a mutually exclusive manner [42–46]. HOXA alterations are typically associated with deletions of TCF7 , RB1 and/or TP53 , and high incidence of mutations affecting members of the JAK/STAT pathway, such as JAK3, STAT5B, and IL7R [20,21,27 ▪ ,41 ▪▪ ]. Furthermore, while CDKN2AB deletions are relatively rare (25%), CDKN1B deletions are frequent (>50%).…”
Section: Immature T-cell Acute Lymphoblastic Leukemias (Etp-all Near ...mentioning
confidence: 99%
“…Blasts may express CD2 and CD4, but these antigens are not required. If CD5 is positive, then it should be expressed in less than 75% of blast cells (Genescà & la Starza, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…If CD5 is positive, then it should be expressed in less than 75% of blast cells (Genescà & la Starza, 2022).…”
mentioning
confidence: 99%
“…As the most common childhood cancer, acute lymphoblastic leukemia (ALL) accounts for 26% of tumors in children under 15% and 8% in adolescents between 15–19 years of age ( Ward et al, 2014 ). ALL is an aggressive and complex disease, and the epidemiological survey data showed that its age-standardized incidence is 0.68/1000,000 ( Yi et al, 2020 ; Genescà and González-Gil, 2022 ). ALL stands for T/B precursor lymphocyte malignancy and blocks lymphocyte differentiation, allowing cells to proliferate and survive abnormally ( Zuckerman and Rowe, 2014 ).…”
Section: Introductionmentioning
confidence: 99%